Pengembangan Media Pembelajaran Interaktif Menggunakan Wordwall Kelas IV Sekolah Dasar - Saputra, Maulana Rafi Rulis; Hermawan, Feri; Setiyawan, Hery (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to develop the use of interactive learning media based on Wordwall on students' understanding and interest in learning. By adopting the ADDIE development model, this study involved fourth grade students of elementary schools in Surabaya and used the R&D research method. Data collection techniques were carried out using literature studies of previous and relevant scientific sources, the results showed that Wordwall media succeeded in creating an interactive, fun, and meaningful learning atmosphere. The validity of the media was rated very well, with a score of 90% for the material aspect, 88.75% for the media aspect, and 82.5% for the language aspect. The practicality test also showed very positive results, with teacher response questionnaires reaching 97.5% and students 96%, both in the very practical category. This finding shows that Wordwall is an effective learning media that is feasible to use in the learning process, and can be a relevant alternative to support learning activities in the digital era. Students' enthusiasm in using this media further strengthens the conclusion that Wordwall can increase the effectiveness of learning in the classroom.